Analysis of the Process of RMB Internationalization with Special Emphasis on the Offshore Bond Markets - Liu, Yunqi (International Journal of Global Economics and Management, 2024)
With rapid economic growth in recent years, China has become the world’s second largest economy. In the context of economic globalization, the process of RMB internationalization is gradually accelerating, and remarkable achievements have been made in cross-border settlement and offshore market. This paper first reviews the relevant theories of currency internationalization and analyzes the historical conditions of the development of RMB internationalization. It reveals the internal and external driving forces of RMB internationalization and sorts out its development context. Taking the offshore bond market as the research object, the currency structure in the international bond market is selected as an index reflecting the degree of currency internationalization, and the determining model of international bond proportion is established. Using the data of 28 countries from 2005 to 2019, the regression analysis shows that a country’s economic size and domestic macroeconomic stability are positively correlated with the level of currency internationalization, while foreign exchange reserves are negatively correlated. According to the model, the difference between the theoretical demand and the actual issuance of RMB international bonds is nearly 10 times. Therefore, it can be inferred that the offshore RMB bond market has great development potential.